The Role of a Visible/Visual Disability in the Clinical Dyad: Issues of Visibility/Invisibility for the Client and Clinician. - Chalfin, Fanny (Psychoanalytic Social Work)
This article discusses disability as a neglected aspect of cultural competency in the diversity literature. It identifies some of the sociocultural concepts that contribute to the avoidance of people with disabilities in the general population, the psychodynamic and psychoanalytic profession, literature, and discourse. Personal and cultural aspects of unanalyzed countertransference and transference are examined. The impact of those internalized sociocultural concepts on the clinical dyad is also explored. Through anecdote, parallel processing, and the literature, it will be shown how some of the transference issues toward the disabled clinician can become assets in the therapeutic alliance.